The Role of ChatGPT in Enabling MSMEs to Compete in the Digital Age - Abu Muna Almaududi Ausat; Hizbul Khootimah Azzaakiyyah; Riko Mersandro Permana; Yasir Riady; Suherlan Suherlan (Innovative: Journal Of Social Science Research, 2023)
SMEs are considered the backbone of the economy as they make significant contributions in creating jobs and building local economies. However, SMEs often face various challenges, especially in facing the digital era. This study aims to identify the role of ChatGPT in facilitating SMEs to compete in the digital era and evaluate the impact of using ChatGPT on the business performance of SMEs. This research is qualitative in nature. The methodology used to collect data included attentive listening and careful documentation of relevant information, which was then subjected to analytical procedures such as data reduction, data display, and conclusion drawing. The study results arrive at the conclusion that in the ever-evolving digital era, MSME players need to be able to compete with large businesses in utilising information technology and harnessing the benefits that such technology provides. ChatGPT can assist MSMEs in increasing their digital presence, optimising marketing efforts, and developing more effective marketing strategies.